Literature Review : Faktor –Faktor yang Mempengaruhi Pola Makan Anak Usia 2-7 Tahun - Ninda Azifati Nurfitri; Rinawati; Vera Yunita; Luvi Dian Afriyani (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
Suboptimal feeding practices and food intake in childhood are associated with poor health outcomes in adulthood. This literature review study aims to profile feeding practices, parental perceptions, and dietary diversity in children aged 2-7 years. The type of research is a study using the Literature Review Study method with the aim of analyzing factors that influence the eating patterns of children aged 2-7 years. The search was conducted electronically using a database from 2020 to 2024. The keywords used were "factors", "PMBA", "ASI", "dietary patterns". The search used the keywords above with the ProQuest Direct database according to the inclusion and exclusion criteria. The inclusion criteria were articles in Indonesian and English, articles that could be accessed in full text in PDF format and articles published in 2022-2024. The exclusion criteria were articles other than in English, could not beaccessed in full text PDF and secondary articles (such as review articles). The search results obtained 9 articles and 4 English articles were selected that could be accessed in full text in PDF format. The framework used is PICO (Population, Intervention, Comparison, Outcome). The research sample of children aged 2-7 years then the articles obtained were reviewed, systematically arranged, comparing one article with another, then discussed with other literature and linked so that they can produce appropriate results. The results of the review of 4 journals showed that in general 27.6% of children were exclusively breastfed until the age of 6 months and 62.1% of children were introduced to solid foods before the age of 6 months. More than 60% of children achieved minimum dietary diversity. Thematic analysis identified four themes, including, Mothers' perceptions of their children's diets, External Influences, Personal Experiences and Choices and Feeding Behavior. In conclusion, based on the results of the literature review that we obtained from the 4 articles, it can be concluded that the factors that influence feeding in children aged 2-7 years are Mothers' Perceptions of Their Children's Diets, external influences, personal experiences, choices and feeding behavior. For health workers, namely midwives, nurses and doctors, it is hoped that they can provide education to mothers and child care providers from an early age so that they can provide a diet appropriate to the age of 2-7 year.   Abstrak Praktik pemberian makan dan asupan makanan yang kurang optimal pada masa kanak-kanak dikaitkan dengan hasil kesehatan yang buruk di masa dewasa. Penelitian metode literatur review ini bertujuan untuk membuat profil praktik pemberian makan, persepsi orang tua, dan keragaman makanan pada anak 2-7. Jenis penelitian merupakan penelitian dengan menggunakan metode Studi Literatur Review dengan tujuan menganalisa faktor-faktor yang mempengaruhi pola makan anak usia 2-7 tahun.Pencarian dilakukan secara elektronik dengan menggunakan database dari 2020 sampai 2024. Keyword yang digunakan adalah “faktor-faktor/factors”, “PMBA”, “ASI”,”pola makan”,. Pencarian menggunakan keyword di atas dengan database ProQuest Direct sesuai dengan kriteria inklusi dan ekslusi. Kriteria inklusi adalah artikel berbahasa Indonesia dan inggris, artikel dapat diakses full text dalam bentuk pdf dan artikel terbitan tahun 2022-2024 Kriteria ekslusi artikel selain berbahasa inggris, tidak dapat diakses full text pdf dan artikel sekunder (seperti artikel ulasan review). Hasil penelusuran diperoleh 9 artikel dan dipilih sebanyak 4 artikel  bahasa inggris yang dapat diakses full text dalam format pdf. Kerangka kerja yang digunakan adalah PICO (Populasi, Intervensi, Comparasion, Outcome). Sampel penelitian anak usia 2-7 tahun selanjutnya artikel yang diperoleh di review, disusun sistematis, membandingkan artikel yang satu dengan uang lain, kemudian dibahas dengan literatur lainnya dan dikaitkan sehingga dapat menghasilkan hasil yang sesuai. Hasil tinjuan dari 4 jurnal menunjukkan bahwa secara garis besar 27,6% anak disusui secara eksklusif hingga usia 6 bulan dan 62,1% anak diperkenalkan dengan makanan padat sebelum usia 6 bulan. Lebih dari 60% anak mencapai keragaman makanan minimum. Analisis tematik mengidentifikasi empat tema, termasuk, Persepsi ibu tentang pola makan anak-anak mereka, Pengaruh Eksternal, Pengalaman Pribadi dan Pilihan dan Perilaku Pemberian Makanan. Kesimpulanya berdasarkan hasil literature review yang kami dapat dari 4 artikel tersebut dapat disimpulkan bahwa faktor-faktor yang mempengaruhi pemberian makan pada anak usia 2-7 tahun adalah Persepsi Ibu terhadap Pola Makan Anaknya, pengaruh eksternal, pengalaman pribadi, pilihan dan perilaku pemberian makanan. Bagi Tenaga kesehatan yaitu bidan, perawat dan dokter, diharapkan dapat memberikan edukasi kepada ibu,pengasuh anak sejak dini agar mereka dapat memberikan pola makan sesuai usia mulai 2-7 tahun.